The law relating to the supervision of banks : a comparison between the Federal Republic of Germany and the Republic of South Africa - Krammig, Andreas (Stellenbosch University, 1998)
ENGLISH SUMMARY: Banks are one of the most important elements in the economic cycle of modem society. As money replaced bartering banks have gradually moved into the pivotal point of the relations between participants in the economic cycle. No project can be realized without money today. On the one hand, there are the investors who, irrespective of the amount, entrust their assets to the banks. On the other hand, there are those whose financial needs require the granting of some form of credit. Banks operating in these contexts clearly bear important responsibilities towards the different parties. A third party, the state, is also interested in a well-functioning banking establishment. Economic stability, without which there can be no political stability, cannot otherwise be ensured. The state is accordingly keenly interested in maintaining the operability of this system. To this end, various laws are made in the respective countries aimed at supervising the banking industry. This work deals with some of the legislation relating to bank supervision in the Federal Republic of Germany and the Republic of South Africa. In the various chapters certain aspects of bank supervision in the two countries are identified, juxtaposed and compared. The reasons for any differences are sought, discussed and where possible explained. From a historical point of view, the two countries developed differently. Nevertheless, the need to regulate this sector through legislative means arose at an early stage in both. Unfortunately, the catalyst for legislative development was mostly some or other financial crisis. Any measures for supervising banks must, to be binding, be constitutional. In this regard much must still be done in South Africa due to the fact that the New Constitution has only been in force since 1996. Thus certain regulations stemming from the Banks Act 90 of 1994 need to be reconsidered in the light of the constitution. Bank supervisory activity is performed by a national institution in both countries. Germany avails itself of an independent authority. However, in South Africa it is one of the tasks of the central bank which has established a specific office for this purpose. Legal and natural persons alike are subject to such supervision. Diverse other government institutions provide support for such supervisory work in both countries. The scope of banking supervision, that is the persons and transactions affected, is broad and also finely meshed. Both systems list a number of banking transactions that are subject to their supervision. This affects all domestic banks and all foreign banks that are domestically active. Access to the banking business is only permitted in both countries after an appropriate license has been granted. The license can be conditional. Moreover, both systems make provision for the revocation of the license in appropriate circumstances. The conducting of banking business without the necessary permission is forbidden in both countries under the threat of legal punishment. It is well recognized in modem society that legal subjects should be protected against the decisions of those who wield state power. The possible remedies of those affected by the decisions of the public authorities responsible for banking supervision in the different countries are investigated in conclusion.
Keywords: Banks and Banking; Financial institutions; Germany; Government policy; South Africa

A Comparative Study of the Shipowner's Lien for Freight - Gazem, Abdelhamid (University of Glasgow, 1991)
The shipping business is an important element for the life of the trade of the different countries of the world. It had a very important role in the past it still has and it will always have, as it is the cheapest means of transportation of goods. However, despite the importance of this element the legal complexities bom out of this business makes it a broad subject of study and research for the lawyers. This is because of the different documents used for the execution of the contract of transport by sea and because of the speed these deals are concluded and the different nationalities of the parties to the contract.